Behavioral coexistence and feeding efficiency drive niche partitioning in European avian scavengers. (8th February 2016) - Moreno-Opo, Rubén; Trujillano, Ana; Margalida, Antoni
Lay Summary: How to share a highly competed common resource efficiently? Within the most diverse guild of avian scavengers in Europe, the study of the individual feeding behavior of 10 species sheds light on the diversity and complementarity of strategies for exploiting carcasses. Pecking rate, time spent eating, prey selection, and feeding efficiency differed between species and age groups. Behavioral and morphological specialization enables resource partitioning at carcasses, leading to a decrease of competition for this resource. Twitter: @rubenmorenoopo Abstract: The mechanisms that determine the evolutionary adaptations of scavengers to carrion exploitation have been well established. In contrast, little is known about coexistence during carrion exploitation based on behavioral traits and considering obligate and facultative species together. This study revisits the hypotheses of behavioral organization within the guild of necrophagous birds in light of the adaptive processes of specialization to carrion exploitation. We used a detailed dataset of observations from high-quality video recordings in the 2 regions with the most diverse and abundant populations of European avian scavengers. Active feeding time varied between species, with the obligate scavengers spending more time eating. The way that scavengers ate the food (i.e., on the ground or carrying away) diverged among species, with species with longer and more pointed beaks and a greater prehensile ability (of talons to grip things) carrying the remains away more often. We recognized the diversity and complementarity of strategies aimed at exploiting the same resource by different species and age classes. Scavenger species were clustered according to the relationship between the time active at the feeding site and the number of feeding pecks, leading to a decrease in competition for resource exploitation, as well as an occupation of specialized trophic niches. The study of active-consumption rates showed that eagles and vultures obtained most and a half, respectively, of their daily energetic requirements from each feeding event, reinforcing the important role of this relevant food source from ecological, evolutionary, behavioral, and conservation standpoints.